Atelectasis in primary graft dysfunction survivors after lung transplantation. Issue 7 (25th April 2021) - Li, David; Abele, Jonathan; Weinkauf, Justin; Kapasi, Ali; Hirji, Alim; Varughese, Rhea; Nagendran, Jayan; Lien, Dale; Doucette, Karen; Halloran, Kieran
Abstract: Background: Primary graft dysfunction (PGD) is an important contributor to early mortality in lung transplant recipients and is associated with impaired lung function. The radiographic sequelae of PGD on computed tomography (CT) have not been characterized. Methods: We studied adult double lung transplant recipients from 2010 to 2016 for whom protocol 3‐month post‐transplant CT scans were available. We assessed CTs for changes including pleural effusions, ground glass opacification, atelectasis, centrilobular nodularity, consolidation, interlobular septal thickening, air trapping and fibrosis, and their relationship to prior post‐transplant PGD, future lung function, post‐transplant baseline lung allograft dysfunction (BLAD), and chronic lung allograft dysfunction (CLAD). Results: Of 237 patients studied, 50 (21%) developed grade 3 PGD (PGD3) at 48 or 72 h. PGD3 was associated with increased interlobular septal thickening ( p = .0389) and atelectasis ( p = .0001) at 3 months, but only atelectasis remained associated after correction for multiple testing. Atelectasis severity was associated with lower peak forced expiratory volume in 1 s (FEV1) and increased risk of BLAD ( p = .0014) but not with future CLAD onset ( p = .7789). Conclusions: Severe PGD was associated with atelectasis on 3‐month post‐transplant CT in our cohort. Atelectasis on routine CT may be an intermediary identifiable stage between PGD and future poor lung function.